JAMES MARK, The Unfinished Revolution. Making Sense of the Communist Past in Central-Eastern Europe: New Haven-London 2010, Yale University Press, 312 s. - Sommer, Vítězslav (Dějiny – teorie – kritika, 2012)
Review